Pharmacokinetic interactions of breast cancer chemotherapeutics with human doxorubicin reductases - Hofman, Jakub; Skarka, Adam; Havrankova, Jana; Wsol, Vladimir (Biochemical pharmacology, 2015)
Paclitaxel (PTX), docetaxel (DTX), 5-fluorouracil (5-FU), cyclophosphamide (CYC) or tamoxifen (TMX) are combined with doxorubicin (DOX) in first-line chemotherapy regimens that are indicated for breast cancer patients. Although the efficacies of these drugs in combination treatments have been demonstrated in clinical practice, their possible interference with DOX metabolism has not been described in detail to date. In the present study, we investigated the possible interactions of human carbonyl reducing enzymes with 5-FU, PTX, DTX, CYC and TMX. First, the reducing activities of carbonyl reducing enzymes toward DOX were tested using incubations with purified recombinant enzymes. In the subsequent studies, we investigated the possible effects of the tested anticancer agents on the DOX-reducing activities of the most potent enzymes (AKR1C3, CBR1 and AKR1A1) and on the DOX metabolism driven by MCF7, HepG2 and human liver cytosols. In both of these assays, we observed that CYC and its active metabolites inhibited DOX metabolism. In the final study, we tracked the changes in AKR1C3, CBR1 and AKR1A1 expression levels following exposure to the tested cytostatics in MCF7 and HepG2 cells. Consequently, no significant changes in the expression levels of tested enzymes were detected in either cell line. Based on these findings, it is feasible to presume that inhibition rather than induction plays a role in the interactions of the tested anticancer agents with DOX-reducing enzymes. In conclusion, our results describe important molecular events that occur during combination breast cancer therapies and might modulate pharmacokinetic DOX resistance and/or behaviour.
Keywords: kinetika; MCF-7 Cells; Drug Interactions; Liver; 3-Hydroxysteroid Dehydrogenases; Doxorubicin; hydroxyprostaglandindehydrogenasy; játra; buňky Hep G2; taxoidy; Alcohol Oxidoreductases; tamoxifen; cyklofosfamid; Carbonyl reducing enzymes; Aldo-Keto Reductase Family 1 Member C3; regulace genové exprese u nádorů; fluoruracil; Fluorouracil; rekombinantní proteiny; Docetaxel; Chemotherapy; Taxoids; Hydroxyprostaglandin Dehydrogenases; protein AKR1C3; Hep G2 Cells; Oxidation-Reduction; Antineoplastic Agents; docetaxel; MFC-7 buňky; Breast cancer; biotransformace; Biotransformation; Isoenzymes; doxorubicin; protinádorové látky; Cyclophosphamide; Humans; Gene Expression Regulation, Neoplastic; izoenzymy; Kinetics; Tamoxifen; aldehydreduktasa; Antineoplastic Combined Chemotherapy Protocols; lékové interakce; oxidace-redukce; protokoly protinádorové kombinované chemoterapie; Aldehyde Reductase; Pharmacokinetic interactions; alkoholoxidoreduktasy; 3-hydroxysteroid dehydrogenasy; lidé; Recombinant Proteins